Schistosoma mansoni: histological analysis of the synergistic interaction between vaccine immunity and praziquantel therapy in the lungs of mice. - Piper, K; Mott, R; McLaren, D (1990)
Naive CBA mice and mice vaccinated 4 weeks previously with gamma-irradiated cercariae of S. mansoni were challenged percutaneously with normal cercariae and then treated with 500 mg/kg body weight of Praziquantel (Pzq). The drug was administered intradermally on day 1 or intramuscularly on day 6, thus targeting against skin stage or lung stage challenge larvae respectively. The skin site of challenge and/or the lungs were removed at various time points to provide samples for histological examination. As reported elsewhere (Flisser, Delgado and McLaren 1989) the efficacy of Pzq was significantly enhanced in vaccinated mice and was influenced by the treatment regime. Histological analysis revealed that when Pzq was administered I/D on day 1 to vaccinated mice, the inflammatory response to challenge differed in extent but not nature from that seen in vaccinated but untreated cohorts. This correlates with worm recovery data showing no (this study), or only marginal synergy between drug treatment and immunity using this regimen of drug treatment (Flisser et al. 1989). Following the day 6 protocol of drug delivery, however, lungs from treated vaccinated mice exhibited many large inflammatory reactions containing trapped challenge larvae. In contrast, lungs from untreated vaccinated mice had only few foci which were small and rarely contained trapped larvae. These data again correlate well with worm recovery data showing that there is a highly significant synergy between vaccination and drug treatment administered at this time (Flisser et al. 1989; this study). It would seem, therefore, that Pzq exacerbates lung phase immunity in the NIMR vaccine mouse model where skin phase immunity predominates and pulmonary attrition is normally minimal. The results are discussed in the light of published data concerning the effector mechanisms thought to characterize skin and lung phase vaccine resistance in the murine model.